2017
DOI: 10.1007/s10237-017-0908-4
|View full text |Cite
|
Sign up to set email alerts
|

On the in vivo function of the mitral heart valve leaflet: insights into tissue–interstitial cell biomechanical coupling

Abstract: There continues to be a critical need for developing data-informed computational modeling techniques that enable systematic evaluations of mitral valve (MV) function. This is important for a better understanding of MV organ-level biomechanical performance, in vivo functional tissue stresses, and the biosynthetic responses of MV interstitial cells (MVICs) in the normal, pathophysiological, and surgically repaired states. In the present study, we utilized extant ovine MV population-averaged 3D fiducial marker da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Dashed lines indicate the full range of each parameter observed across six total MV specimens in previous studies that have utilized this model form. 21,22,60,77 In the context of our novel image-based strain estimation method, while the use of a material model is important to regularize the resulting stretch field and impose physical realism, these results demonstrate that the accuracy of the method is only mildly dependent on the specific choice of material parameters and that the method consistently delivers stretch estimates within 10% of their true value ) .…”
Section: Figure A2mentioning
confidence: 76%
See 4 more Smart Citations
“…Dashed lines indicate the full range of each parameter observed across six total MV specimens in previous studies that have utilized this model form. 21,22,60,77 In the context of our novel image-based strain estimation method, while the use of a material model is important to regularize the resulting stretch field and impose physical realism, these results demonstrate that the accuracy of the method is only mildly dependent on the specific choice of material parameters and that the method consistently delivers stretch estimates within 10% of their true value ) .…”
Section: Figure A2mentioning
confidence: 76%
“…To maximally account for intersubject variability in material properties, each parameter was varied sufficiently to span beyond the full range observed across six total MV specimens in four previous studies that have utilized the same fiber-based structural model. 21,22,60,77 For each case, E ub was adjusted such that total fiber recruitment occurred at approximately 400 kPa of stress, as this quantity has been shown to be consistent across heart valve tissues. 75,92 The results showed that over the observed range of material responses, our novel image-based strain determination method provided stretch estimates with an average absolute error less than 10% ( Figure A2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations